For I am woorthyer by muche then he: The functions of first person singular utterances in Early Modern English debate verse - Hanna Salmi (University of Gothenburg; Nordic Association of English Studies, 2022)
Very little linguistically oriented work has so far been done on debate poetry. However, debates are an interesting source for studying conflict interactions, a topic of increasing relevance. While literary representations of conflict will not show us how disputes were carried out in reality, they can shed light on which features were salient enough to be used as stylised markers of interactivity in literary texts. As first and second person pronouns are well-known markers of interactivity and involvement, this paper examines the first person utterances in a small corpus of debate poetry, available from the EEBO database. The analysis has two parts: a quantitative analysis, where the represented dialogue and the narrator’s frame story are analysed as separate layers (Clark 1996), and a qualitative analysis focusing on the dialogue sections only. The quantitative analysis involves locating all instances of the first person singular pronoun in subject form, combined with the associated verb phrase. The verbs are then classified according to semantic domains (Biber et al. 1999) and the layer of text they occur in. This quantitative part is designed to allow comparisons between the layers, but also between debate poetry and the genre of controversies. The qualitative section, on the other hand, investigates certain moves commonly found in the dialogues, along with the verb types most frequently associated with each move.